Collaborate or Compete: Examining Manufacturers' Replacement Strategies for a Substance of Concern. Issue 9 (5th May 2017) - Kraft, Tim; Raz, Gal
Abstract : The recent proliferation of media reports on substances of concern has increased consumer fears, sparked scientific debate, and highlighted the need for stronger chemical regulations. When a substance of concern is identified (e.g., bisphenol‐A (BPA) in reusable water bottles), manufacturers face difficult trade‐offs in deciding whether to proactively replace the substance in their products or to defer replacement and wait to see if regulation occurs. In this study, we examine when opportunities exist for manufacturers to avoid competitively replacing (i.e., making their replacement decisions on their own), and instead, collaborate to replace a substance of concern. We model a vertically differentiated market consisting of a high‐end manufacturer and a low‐end manufacturer, both of whom sell a product that contains a substance of concern. Our analysis investigates how market dynamics (competition and consumer preferences) and external factors (replacement costs and regulatory uncertainty) influence manufacturers' collaboration, replacement, and pricing decisions. We find that when the manufacturers do not collaborate, the high‐end manufacturer can use the presence of a substance of concern to dominate the market by capturing more demand and often charging a higher price for his product than the low‐end manufacturer. Collaboration is possible when there is either a shared fixed cost savings for both manufacturers or an opportunity for the low‐end manufacturer to benefit his competitive position by motivating the high‐end manufacturer to collaborate. From a consumer perspective, although collaboration reduces consumer exposure to the substance of concern, it can decrease consumer surplus when the replacement substance is very expensive.